PENGARUH LEVERAGE, KUALITAS AUDIT, DAN LAIN-LAINYA TERHADAP AGRESIVITAS PAJAK - Yulius Kurnia Susanto; Alvin (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to analyze the effect of leverage, audit quality, size, family ownership, capital intensity, profitability and liquidity on tax aggressiveness. The sampled of this study are manufacturing company listed on the Indonesia Stock Exchange during year 2018-2020. The sample in this study was obtained by the purposive sampling method. There are 55 companies chosen as the final samples. The hypothesis of this study is tested using the multiple regression analysis. The results of this study indicate that profitability has an influence on tax aggressiveness in Indonesia. However, leverage, audit quality, size, family ownership, capital intensity and liquidity have no effect on tax aggressiveness in Indonesia.